Isolation and identification of phytophthora sp. and pythium sp. from durian orchard in Chumphon Province, Thailand - Suksiri, S.; Laipasu, P.; Soytong, K.; Poeaim, S. (My University, 2018)
The major problem of durian cultivation are root and stem rot disease caused by Phytophthora and Pythium species. Therefore, the pathogens were isolated, identified, and found the virulent pathogenic fungi that isolated from soil planted to durian in Chumphon province. The pathogens were studied on morphological and molecular analysis based on internal transcribed spacer (ITS)-nrDNA sequence. Ten isolates were confirmed as Phytophthora palmivora, Pythium cucurbitacearum, Pythium deliense, Pythium splendens, Mortierella chlamydospora, Mortierella capitata and Mortierella sp. The pathogenicity test was done by detached leaf method in Monthong durian variety. It found that P. palmivora and P. cucurbitacearum were high pathogenic isolates. Moreover, P. splendens was infected and produced symptoms on leaves. It is the first report of P. splendens as pathogenic to durian.
Keywords: internal transcribed spacer; Phytophthora sp.; Pythium sp.; root and stem rot disease